2023
DOI: 10.1111/jpn.13868
|View full text |Cite
|
Sign up to set email alerts
|

Influences of flavonoid (quercetin) inclusion to corn‐soybean‐gluten meal‐based diet on broiler performance

Abstract: Quercetin (a predominant flavonoid) is considered to have antimicrobial and antioxidant properties. This trial was conducted to evaluate the impact of graded doses of quercetin (QS) on growth efficiency, nutrient retention, faecal score, footpad lesion score, tibia ash and meat quality. In a 32‐day feeding test, a total of 576 1‐day‐old Ross 308 broilers (male) were allocated arbitrarily with an average body weight of 41 ± 0.5 g. The trial had four dietary treatments with eight repetitions of 18 birds per pen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Incorporating quercetin into the graded-level diet resulted in enhanced growth efficiency, absorption, meat quality and tibia ash levels, suggesting it as a potential additive in broiler production (Biswas, Cho, Ahn, et al, 2023).…”
Section: Quercetin As Pfasmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating quercetin into the graded-level diet resulted in enhanced growth efficiency, absorption, meat quality and tibia ash levels, suggesting it as a potential additive in broiler production (Biswas, Cho, Ahn, et al, 2023).…”
Section: Quercetin As Pfasmentioning
confidence: 99%
“…Researchers found that giving supplemental plant extract to weaning piglets enhanced their efficiency, nutrient absorption and gut barrier integrity (Yan, Zhang, et al, 2012). The hydroxyl group of the bioactive substances present in the herb extract demonstrates antimicrobial properties because it can attach to protein molecules of bacteria, causing the release of essential cell components (Bessam & Mehdadi, 2014). Antibacterial substances obtained from plant polyphenols modify the intestinal microbiota of animals, which also shields animals from competing for essential nutrients and results in a decrease in harmful substances that inhibit rapid development and nutrient utilization (Klose et al, 2010).…”
Section: Introductionmentioning
confidence: 99%